2008
DOI: 10.3748/wjg.14.6662
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling: Canonical molecular changes and clinicopathological features in sporadic colorectal cancers

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
1
17
1
Order By: Relevance
“…However, the clinicopathological characteristics of SPRR3 have not been investigated in other types of cancers, including colorectal cancer. We have previously reported the association of several genes with molecular alterations in colorectal tumorigenesis (8). Surprisingly, in contrast to the findings in ESCC, SPRR3 was frequently and dramatically upregulated in colorectal cancers.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…However, the clinicopathological characteristics of SPRR3 have not been investigated in other types of cancers, including colorectal cancer. We have previously reported the association of several genes with molecular alterations in colorectal tumorigenesis (8). Surprisingly, in contrast to the findings in ESCC, SPRR3 was frequently and dramatically upregulated in colorectal cancers.…”
Section: Discussioncontrasting
confidence: 48%
“…To investigate the molecular changes associated with colorectal tumorigenesis, we analyzed gene expression patterns in 84 patients with sporadic colorectal cancer by using a microarray (8). Among 1263 differentially expressed genes, SPRR3 was shown to be associated with molecular changes, and we therefore examined the expression level of SPRR3 in colorectal cancers.…”
Section: Sprr3 Is Upregulated In Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…LDHA expression is representative for increased pyruvate metabolism, which is associated with enhanced glycolysis. In line with the observed increase in expression of glycolysis and associated pathways is an apparent increase in LDHA expression in adenomas, while no change is observed during malignant transformation [17,18]. Hypoxia is one of the mechanisms that regulate transcriptional changes to support these metabolic alterations [19].…”
Section: Processes Reprogrammed During Adenoma Development and Genomimentioning
confidence: 52%
“…Thence, TRAPPC9 may adjust the function of trans-Golgi and the formation of autophagosome during cancer development. Studies have confirmed that transcription of TRAPPC9 exists in various cell lines and tumor tissues, and clinical studies have also reported TRAPPC9 transcripts with human breast [20] , colon cancer [21] , osteosarcoma [22] , and lymphoma [23,24] . Recent some genetic susceptibility studies of lung cancer have focus on single nucleotide polymorphisms (SNPs) in lncRNAs.…”
Section: Introductionmentioning
confidence: 81%